Smoking cessation and its relationship with religiosity: a review of literature - Azmi, Junainah; Syed Elias, Sharifah Munirah; Nurumal, Mohd. Said; Mohd Mokhtar, Hanida Hani (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
This study aims to systematically review the literature regarding the relationship between religiosity/spirituality and smoking behaviour. Systematic searches were conducted to identify the literature published since 2013-2019 based on sets of inclusion and exclusion criteria. Four electronic databases were used to identify the literature, including Scopus, Science Direct, ProQuest and PubMed. The search was limited to full-text articles/ review papers and in English or Malay language only. Articles on smoking prevention and other nicotine delivering devices such as vape or electronic cigarette were excluded from the study. Initially, 26,938 articles were retrieved, but only 12 were finalised to be critically appraised. Out of the 12 studies, five studies revealed a significant relationship between religious/spiritual activities and cessation while the others showed an inverse association between religiosity and smoking. Religiosity/spirituality played an essential role in influencing smoking behaviour, making it an important vehicle to complement other existing tobacco control efforts. Limited studies were focusing on the Islamic religion despite the growing number of the Muslim population worldwide. Thus further research on the integration of Islamic religion in the smoking cessation program is highly recommended, especially in a Muslim country like Malaysia.